Efektivitas Model Pembelajaran Missouri Mathematics Project Berbasis GeoGebra Terhadap Kemampuan Pemecahan Masalah Siswa - Ni Putu Asri Wijayanti; I Putu Pasek Suryawan (Universitas Pendidikan Ganesha, 2019)
This study was aimed to determine the effect of MMP learning model assisted by GeoGebra towards students’ mathematics problem solving. The design of this study used post-test only control group design. The population of this study was eighth grade studens at SMPN 2 Mendoyo in academic year 2019/2020 namely 222 people were distributed into 7 classes. The data of students’ problem solving ability were analyzed using One Way ANAVA test and further test using Scheffe test with a significance level of 5%. The analysis showed that : first, there were differences in problem solving ability between the experimental class 1, experimental class 2 and the control class; second, the mathematical problem solving ability of experimental class 1 was higher than the control class (Fhitung =27,14636 > F’= 6,2); third, the mathematicasl problem solving ability of experimental class 2 was higher than the control class Fhitung =7,3 > F’= 6,2); fourth, the mathematical problem solving ability of experimental class 2 was higher than the control class (Fhitung = 6,7465 > F’ = 6,2). It can be concluded that there was MMP learning model based on GeoGebra effective in improving students’ mathematical problem solving ability.